The Importance of Organizational Commitment as a Mediation in Improving the Performance of Specialist Doctors: The Effect of Transformational Leadership and Work Discipline - Abdullah️ Abdullah️; Djoko Soelistya; Tri Cicik Wijayanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The role of the business world in hospitals is full of challenges in providing services to patients, especially in health services. Hospitals have a burden of demands to be able to absorb the aspirations that develop in the community and also have to make adjustments in services to improve hospital performance, because the competition that occurs in the strict health service business demands that hospitals as service providers are required to always pamper patients. by providing the best service, so that the performance of specialist doctors must be really good in supporting the quality of service, with a transformational leadership style and good work discipline but must be supported by consistent organizational commitment in the hospital, The following research uses a quantitative approach that has a population of all specialist doctors and the sample is 75 respondents called the saturated sample, while the analysis model uses the SmartPLS 3.0 analysis program. The following research results that (1) transformational leadership style has a direct effect on the performance of specialist doctors, although not significantly; (2) transformational leadership style has a direct effect on organizational commitment, although it is not significant; (3) Work discipline has a direct effect on organizational commitment; (4) Work discipline has a direct effect on the performance of specialist doctors; (5) organizational commitment has a direct effect on the performance of specialist doctors, while the results of the indirect effect test show that (6) transformational leadership style can have a direct effect on the performance of specialists even without going through organizational commitment as well (7) work discipline can have a direct effect on the performance of specialist doctors even without going through organizational commitment.